Evaluasi Sistem Penirisan Tambang di PT Vitrama Properti Desa Air Mesu Kabupaten Bangka Tengah - Riztia Ramadhanti; Delita Ega Andini; Haslen Oktarianty (Jurusan Teknik Pertambangan Universitas Bangka Belitung, 2021)
PT Vitrama Properti applies mine dewatering system by making open channel. The open channel got silting because many solid particles have deposited causing the mine road become flooded. The method used is quantitative method by evaluating and analyzing dewatering system. The data taken is in the form of coordinate data, actual discharge, channel dimensions and the time for sediment deposition on settling pond. Catchment area is 42.4 ha. Based on the calculation of rainfall data and rainfall analysis with the gumbell method, the maximum planned rainfall value is 183.9 mm/day with a rain intensity is 63.75 mm/day, the maximum total discharge is 156,193.92 m3 /day or 1.8078 m3 /day. The surface width of the new channel is 1.7 m, the bottom width is 0.5 m and height is 1 m. The new settling pond dimension have total design volume of 3,292.5 m3 . The time for dredging the sediment material in the settling pond is every one or two years when the sediment material in compartment one has deposited as much as 60% of settling pond volume